Predicting Therapeutic Response in Pediatric Ulcerative Colitis—A Journey Towards Precision Medicine - Ruben J. Colman; Jasbir Dhaliwal; Jasbir Dhaliwal; Michael J. Rosen; Michael J. Rosen (Frontiers in Pediatrics, 2021)
Ulcerative colitis (UC) is a disabling disease, characterized by chronic inflammation of the colon, with a rising prevalence worldwide in the pediatric age group. Although UC presents in children with varying severity, disease extent, and comorbidities, initial treatment is essentially uniform, consisting of 5-aminosalicylate drugs with corticosteroid induction for those with moderately to severely active disease. With the advent of anti-tumor necrosis factor (TNF) biologic therapy and several new biologics and small-molecule drugs for UC, precision medicine approaches to treatment are needed to more rapidly achieve sustained remission, restore quality of life, normalize development, and limit exposure to toxic corticosteroids in children with UC. Here, we review available data on clinical, biochemical, histopathologic, and molecular predictors of treatment response in UC. We also address known predictors and special treatment considerations in specific relevant scenarios such as very-early-onset UC, acute severe UC, ileal pouch anal anastomosis, and UC with concomitant primary sclerosing cholangitis. The review concludes with a prediction of how machine learning will integrate multimodal patient data to bring precision medicine to the bedside of children with UC in the future.